Circulating Vitamin D and Colorectal Cancer Risk: An International Pooling Project of 17 Cohorts. (14th June 2018) - McCullough, Marjorie L; Zoltick, Emilie S; Weinstein, Stephanie J; Fedirko, Veronika; Wang, Molin; Cook, Nancy R; Eliassen, A Heather; Zeleniuch-Jacquotte, Anne; Agnoli, Claudia; Albanes, Demetrius; Barnett, Matthew J; Buring, Julie E; et al.
Abstract: Background: Experimental and epidemiological studies suggest a protective role for vitamin D in colorectal carcinogenesis, but evidence is inconclusive. Circulating 25-hydroxyvitamin D (25(OH)D) concentrations that minimize risk are unknown. Current Institute of Medicine (IOM) vitamin D guidance is based solely on bone health. Methods: We pooled participant-level data from 17 cohorts, comprising 5706 colorectal cancer case participants and 7107 control participants with a wide range of circulating 25(OH)D concentrations. For 30.1% of participants, 25(OH)D was newly measured. Previously measured 25(OH)D was calibrated to the same assay to permit estimating risk by absolute concentrations. Study-specific relative risks (RRs) for prediagnostic season-standardized 25(OH)D concentrations were calculated using conditional logistic regression and pooled using random effects models. Results: Compared with the lower range of sufficiency for bone health (50–<62.5 nmol/L), deficient 25(OH)D (<30 nmol/L) was associated with 31% higher colorectal cancer risk (RR = 1.31, 95% confidence interval [CI] = 1.05 to 1.62); 25(OH)D above sufficiency (75–<87.5 and 87.5–<100 nmol/L) was associated with 19% (RR = 0.81, 95% CI = 0.67 to 0.99) and 27% (RR = 0.73, 95% CI = 0.59 to 0.91) lower risk, respectively. At 25(OH)D of 100 nmol/L or greater, risk did not continue to decline and was not statistically significantly reduced (RR = 0.91, 95% CI = 0.67 to 1.24, 3.5% of control participants). Associations were minimally affected when adjusting for body mass index, physical activity, or other risk factors. For each 25 nmol/L increment in circulating 25(OH)D, colorectal cancer risk was 19% lower in women (RR = 0.81, 95% CI = 0.75 to 0.87) and 7% lower in men (RR = 0.93, 95% CI = 0.86 to 1.00) (two-sided P heterogeneity by sex = .008). Associations were inverse in all subgroups, including colorectal subsite, geographic region, and season of blood collection. Conclusions: Higher circulating 25(OH)D was related to a statistically significant, substantially lower colorectal cancer risk in women and non–statistically significant lower risk in men. Optimal 25(OH)D concentrations for colorectal cancer risk reduction, 75-100 nmol/L, appear higher than current IOM recommendations.